A ARISTOCRACIA OPERÁRIA E OS FUNDOS DE PENSÃO | The labor aristocracy and the pension funds (Trabalho & Educação, 2016)
The current text seeks to understand the labor aristocracy process in England and its formation in the late Brazilian capitalism, denoting how this labor class fraction performs an essential role to subordinate the work class set to the purposes of the Capital. It is noted how the labor aristocracy can shift the desideratum of the capital confrontation to an adequacy and accommodation position to the status quo through the mediation of the apology of counter-reformation of the social security and the constituent of the complementary social security, in which the pension funds appear as the reflex of the harmless try in humanizing the capitalism before the corporative governance, the social responsibility, the socioenvironmental sustainability, the ethical funds and the pre-fund retirement systems. Through the ideology of social inclusion and the need of income redistribution, the labor aristocracy plays the elementary function in the orchestrated constructions by the governments of Lula and Dilma Rousseff. However, the economic crisis reveals the impossibility of offering an human face to capitalism and puts on evidence the essential truth of the capital system, wherein the business management with social responsibility manifests itself as a fraudulent administration from the managers involved in the denounces from Lava Jato and in the illegal administration of the complementary social security of the workers, e.g. Postalis. __No decorrer deste texto, busca-se entender o processo de constituição da aristocracia operária na Inglaterra e sua formação no desenvolvimento do tardio capitalismo brasileiro, denotando como essa fração da classe operária desempenha papel essencial para subordinar o conjunto da classe trabalhadora aos propósitos do capital. Nota-se como a aristocracia operária consegue deslocar o desiderato de enfrentamento do capital para uma posição de adequação e acomodação ao status quo pela mediação da apologia da contrarreforma da Previdência Social e da constituição da Previdência complementar, em que os fundos de pensão comparecem como reflexo da inócua tentativa de humanização do capitalismo mediante a governança corporativa, a responsabilidade social, a sustentabilidade socioambiental, os fundos éticos e a aposentadoria por capitalização. Por meio da ideologia da inclusão social e da necessidade de redistribuição de renda, a aristocracia operária desempenha função elementar nas obras orquestradas pelos governos Lula e Dilma Rousseff. No entanto, a crise econômica desvela a impossibilidade de oferecer uma face humana ao capitalismo e evidencia a verdadeira essencialidade do sistema do capital, em que a gestão empresarial com responsabilidade social se manifesta como uma administração fraudulenta dos gestores envolvidos nas denúncias da Lava Jato e na ilícita administração da Previdência complementar dos trabalhadores, como, por exemplo, na Postalis.